Industrial slowdown and small-scale sector - Sathe, Dhanmanjiri (2002)
A preliminary survey of small-scale industrial units in and around Pune shows that a large proportion of them have suffered a fall in sales, to which they have responded by cutting down labour but only rarely by reducing wages. - Reproduced.
Keywords: Small scale industry